Perceived level of stress and coping strategies among International Islamic University Malaysia (IIUM) nursing students - Cho, Cho Zaw; Ibrahim, Mohd Zahid (SAS Publishers, India, 2018)
Nursing students are experiencing stress on a daily basis due to their academic challenges. The effective use of coping strategies is important in handling stress and academic achievement. This study aims to identify the perceived level of stress, and their coping strategies among IIUM nursing students as well as their academic achievement. A descriptive cross-sectional design was used and the data were collected from 2nd, 3rd and 4th year nursing students from IIUM Kuantan (N=128). A set of questionnaires with sociodemographic data, Perceived Stress Scale and Adolescent Coping Orientation for Problem Experiences were used as the instruments. The data were analysed by using SPSS version 19.0 with descriptive and inferential statistic (Chi square test). 7 (5.5%) of students have low level stress, 109 (85.1%) moderate level, and 12 (9.4%) high level stress. Under twelve domains, the students used different coping strategies and it showed 119 (93%) never smoke, 94 (73.4%) never used drugs, 83 (64.8%) never stay away from home, 82 (64.1%) seek spiritual support by talking to rabbi and praying in times of having stress. For academic performance, 1 (0.8%) of students have CGPA 3.51-4.00, 25 (19.5%) have CGPA 2.51-3.00, 102 (79.7%) with CGPA 3.01-3.50. No significant association between stress level and academic performance (CGPA) with p-value > 0.05 (0.447). However, 102 (86.9%) of students with moderate stress level have moderate CGPA (3.01-3.50). Majority of them apply positive and avoid negative behaviours. The students with stress still have their academic achievement and it may depend on individual students, and the use of coping strategies in facing stress, thus further study is recommended in the related area.